2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30636
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students' Writing Skills by Integrating Prototyping Activities in their Writing Course

Abstract: Writing is the most important means of communication in the engineering field. Although understanding the content of an engineering discipline is very important, engineers become much more appreciated if they know how to convey their expertise to a variety of audiences. This paper reports on a collaboration between a writing professor and Engineering Enrichment Program at an international branch campus in the Middle East. Over the course of three semesters, a technical and business writing course was redesigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Because ENGL 210 is a general technical writing and communication course that can be taught across all disciplines, there are numerous approaches English instructors may use. Some focus on content and assessments better suited to business settings -newsletters, memos, incident reports, and business proposals -while others have introduced ideation presentations and prototyping [7].…”
Section: A Radical Collaborationmentioning
confidence: 99%
“…Because ENGL 210 is a general technical writing and communication course that can be taught across all disciplines, there are numerous approaches English instructors may use. Some focus on content and assessments better suited to business settings -newsletters, memos, incident reports, and business proposals -while others have introduced ideation presentations and prototyping [7].…”
Section: A Radical Collaborationmentioning
confidence: 99%
“…The end of semester project deliverables consisted of the prototype, a poster describing the product and a brief video inviting the viewer to invest in the product. Student surveys showed that the entrepreneurial aspect of the project inspired students to be better communicators [32].…”
Section: Literature Reviewmentioning
confidence: 99%